Effects of Dietary Additives on Nitrogen Balance, Odor Emissions, and Yolk Corticosterone in Laying Hens Fed Low-Protein Diets - Ju-Yong Song; Yun-Ji Heo; Jina Park; Hyun-Kwan Lee; Yoo Bhin Kim; Byung-Yeon Kwon; Da-Hye Kim; Kyung-Woo Lee (Animals)
The objective of this study was to evaluate the effects of various feed additives on odor emissions, gut health, and stress responses in laying hens fed low-protein diets. Four commercially available functional feed additives (Bacillus subtilis, protease, saponin, and thyme-based essential oil) were selected for this study. A total of 288 Hy-Line brown laying hens aged 49 weeks were randomly fed on one of six experiment diets: a 16% standard crude protein diet, a 12% low-crude-protein (LCP) diet, and LCP diets supplemented with Bacillus-based probiotic, protease, saponin, or thyme-based essential oils prepared for 8 weeks. Each treatment had eight replicates with six birds per replicate. Lowering crude protein levels affected the laying performance, nitrogen balance, odor production (i.e., ammonia), and nutrient digestibility but did not alter eggshell quality or fecal short-chain fatty acids. Dietary additives added into the LCP diet did not affect the laying performance, egg qualities, and nitrogen balance but increased crude ash digestibility compared with the LCP-diet-fed laying hens. Branched-chain fatty acids tended to be higher in all laying hens fed low-CP diets, irrespective of feed additives. Notably, low vs. standard protein diets tended to increase yolk corticosterone levels, which is an indicator of stress responses in chickens. This low-CP-mediated increase in yolk corticosterone was partially decreased by 20.8–48.6% on average, depending on the additives used. Our study suggests that low-protein diets could effectively lower nitrogen excretion and odor emissions. However, adding dietary additives into low-protein diets has minimal effects on low-CP-diet-fed laying hens, which needs further studies to clarify the role of low-crude-protein diets and dietary additives in modulating hindgut fermentation via shaping the gut microbiota and stress responses of laying hens.